Mycosynthesis of zinc oxide nanoparticles using Pleurotus floridanus and optimization of process parameters. Issue 9 (1st May 2021) - Rafeeq, C.M.; Paul, Elizabeth; Vidya Saagar, E.; Manzur Ali, P.P.
Abstract: Zinc nanoparticles are ideal candidates for biomedical applications due to their exceptional properties and biocompatible nature. The conventional methods are unsuitable for biomedical applications owing to the use of toxic chemicals during synthesis. In this context, the synthesis of biocompatible nanoparticles using plants and microorganisms are gaining more attention. In the present study, the mycosysnthesis of zinc oxide nanoparticles were carried out using P. floridanus culture filtrate employing four different methods. The spectral analysis of the samples revealed that the method described by Malek et al. is an efficient method for the synthesis of zinc nanoparticles using mushroom culture extract. The zinc nanoparticles exhibited absorption maxima at 360 nm. The optimum pH and substrate concentration were identified to be 10 and 300 mM respectively. TEM analysis of the synthesized nanoparticles revealed that they have a spherical shape and the SAED analysis confirmed the crystalline nature of the nanoparticles with an average size of 7 nm. The stoichiometric mass percentages of zinc and oxygen were determined using EDAX and found to be 80.34% and 19.66%, respectively which corresponds to the mass percentage for pure zinc oxide nanoparticles. The XRD analysis confirmed that the synthesized nanoparticles had a hexagonal wurtzite structure. Graphical abstract: Image 1